Soybean Fermentation Broth Value-Added Phosphorus Fertilizer Boosts Crop Growth via Improved Soil Phosphorus Availability and Rhizosphere Microbial Activity - Xinyi Zhang; Danyi He; Wuzhihui Huang; Tingyi Wang; Lansheng Deng (Agriculture)
Excessive application of phosphate fertilizers exacerbates water pollution, while the low phosphorus availability in acidic soils results in diminished phosphorus utilization efficiency of crops. This study conducted a maize pot experiment to investigate the effects of soybean fermentation broth value-added phosphorus fertilizer (SFB-VAPF) on soil phosphorus availability and microbial communities in acidic lateritic red soils during the 31-day seedling stage to determine its growth promotion efficacy. Conducted in Guangzhou, China, under greenhouse conditions, the experimental design comprised 11 treatments: CK (no fertilizer), treatments with P alone at two levels (0.05 and 0.15 g·kg−1), and eight SFB-VAPF treatments combining each P level with four dilutions of soybean fermentation broth (SFB; 100-, 300-, 500-, and 700-fold dilutions). Each treatment had five replications. Application of SFB-VAPF significantly improved the soil chemical attributes, enzyme activities, and promoted maize growth and nutrient accumulation. Compared to the high-P treatments (0.15 g·kg−1 P), low-P SFB-VAPF demonstrated superior enhancement of the soil organic matter (SOM), available nutrients, maize biomass, and nutrient accumulation. The treatment combining 0.05 g·kg−1 P and 100-fold diluted SFB significantly increased the acid phosphatase activity (ACP) by 28.01% and the AP content by 69.63%, while achieving the highest maize biomass. Although SFB-VAPF application reduced the microbial species richness, the combinations of low P with high SFB and high P with low SFB enhanced both the community structural diversity and distribution evenness. SFB-VAPF application reduced the abundance of Alphaproteobacteria, while the Gammaproteobacteria abundance significantly increased in the low-P SFB-VAPF groups. The microbial beta diversity analysis demonstrated that combining 0.05 g·kg−1 P with SFB significantly altered the microbial community structure. The key driving factors included soil EC and SOM, AP, Al-P, and Fe-P contents, with AP content exerting an extremely significant influence on the bacterial community composition and structure (p ≤ 0.001). This study demonstrates that SFB-VAPF enhances soil phosphorus availability, and improves the structural diversity and distribution evenness of microbial communities, thereby promoting crop growth. Critically, SFB synergistically enhances the efficiency of low-concentration phosphorus fertilizers.